2022
DOI: 10.1088/1755-1315/976/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

The potency of endophytic fungi isolated from Hippobroma longiflora (L) G. Don as an antioxidant sources

Abstract: Endophytic fungi are friendly microbes colonizing in plants and play an effective role in plant-environment interactions. They produce valuable secondary metabolites that both plants and human beings can benefit from such products. In this study, an antioxidant-producing endophytic fungi were screened and identified from the leaves of Hippobroma longiflora (L.) G. Don which is one of the traditional medicinal plants. The objective of this study to evaluate the antioxidant activity of ethyl acetate extracts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Penicillium steckii was isolated before as an endophytic fungus associated with mangroves (Chen et al, 2021a;Chen et al, 2021b) and banana leaves (Zakaria and Aziz, 2018). However, this strain was repeatedly reported from marine sources, such as sediment samples (Wu et al, 2021), sponges, and deep-sea coral (Hu et al, 2022;Shin et al, 2016;Yao et al, 2021). Nemania bipapillata was recently reported as an endophyte of Vaccinium dunalianum Wight leaves along with P. capitalensis (Fan et al, 2020).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Penicillium steckii was isolated before as an endophytic fungus associated with mangroves (Chen et al, 2021a;Chen et al, 2021b) and banana leaves (Zakaria and Aziz, 2018). However, this strain was repeatedly reported from marine sources, such as sediment samples (Wu et al, 2021), sponges, and deep-sea coral (Hu et al, 2022;Shin et al, 2016;Yao et al, 2021). Nemania bipapillata was recently reported as an endophyte of Vaccinium dunalianum Wight leaves along with P. capitalensis (Fan et al, 2020).…”
Section: Discussionmentioning
confidence: 85%
“…The genus Phyllosticta is known to inhabit a wide host range (Zhu et al, 2021). Particularly, P. capitalensis was found inhabiting the healthy leaves of Tibouchina granulosa (Golias et al, 2020), Loropetalum chinense (Zhu et al, 2021), and Hippobroma longiflora (Widjajanti et al, 2021). Furthermore, Daldinia eschscholtzii is known as a wood-inhabiting endophyte, which is most commonly distributed in the tropical region (Stadler et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Quinone derivative (2,6-Dimethyl-3-(methoxymethyl)-p-benzoquinone), and alkaloid (N-Di-dehydrohexacarboxyl-2,4,5trimethylpiperazine) were also found comprising 10% each. Fungi have been found to create secondary metabolites such as aromatic chemicals, alkaloids, amino acids, fatty acids, phenolic compounds, and quinone derivatives (Brambilla et al, 1988;Nishina et al, 1991;Cole et al, 2003;Leyden et al, 2007;Dhahir et al, 2012;Adedoyin et al, 2013;Zabka and Pavela, 2013;Evidente et al, 2014;Li et al, 2014;Dheeb, 2015;Kareem et al, 2015;Chandra and Arora, 2016;Gao et al, 2016;Mollavali et al, 2016;He et al, 2017;Pathak et al, 2018;Chen et al, 2021;Widjajanti et al, 2022). Species of Alternaria, Aspergillus, Claviceps, Fusarium, and Penicillium are the most active fungi producing approximately 15,600 fungal metabolites (Sulyok et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics, antimicrobials, antioxidants, antiviral, anti-inflammatory, enzyme inhibitors, cytotoxic, hypercholesteremic, immunomodulators, and immunosuppressive medicines have primarily been examined in fungi (Naher et al, 2021;Conrado et al, 2022). Secondary metabolites, such as aromatic compounds, alkaloids, amino acids, fatty acids, phenolic compounds, and quinone derivatives have been recorded to be produced by fungi in several kinds of literature (Brambilla et al, 1988;Nishina et al, 1991;Cole et al, 2003;Leyden et al, 2007;Dhahir et al, 2012;Adedoyin et al, 2013;Zabka and Pavela, 2013;Evidente et al, 2014;Li et al, 2014;Dheeb, 2015;Kareem et al, 2015;Chandra and Arora, 2016;Gao et al, 2016;Mollavali et al, 2016;He et al, 2017;Pathak et al, 2018;Chen et al, 2021;Widjajanti et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Extraction and isolation of compounds of fungal endophytes is efficient because of the short cultivation time [29,30]. The results of the researches describe that metabolites of fungal endophytes isolated from medicinal plants have shown that most of their secondary metabolites have unique chemical structures and they can act as antibacterials [32][33], antioxidants [34][35][36], antifungals [37][38][39], anticancers [40], antidiabetics, antihyperlipidemics [41], antimalarials [43], antihypertensives [44], and antihypercholesterolemics [45,46]. Studies on endophytic fungi isolated from sungkai plant parts have also been reported, such as the leaves and roots.…”
Section: Introductionmentioning
confidence: 99%